IMPROVEMENT OF STRUCTURE HEREDITY OF PISTONS OF HYPOEUTECTIC SILUMIN A K 5M - V. Ju. Stezenko; S. L. Radjko (Литьë и металлургия)
The technology of improvement of structure heredity in pistons of hypoeutectic silumin is worked out.